High-fluorescence modulatable carbon quantum dot as well as preparation method and application thereof
By adjusting the ratio of solvent, carbon source and additives, high fluorescence modulated carbon quantum dots are prepared, which solves the problems of low fluorescence quantum yield, short lifetime and poor compatibility of existing carbon quantum dots, and achieves high efficiency and stable fluorescence performance and good material compatibility.
Patent Information
- Application Number
- CN202411993746.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The fluorescence quantum yield of existing carbon quantum dots is low, the fluorescence lifetime is short, and the compatibility with other materials is poor, which affects the overall performance of the material.
By adjusting the ratio of solvent, carbon source and additive, a highly fluorescent modulated carbon quantum dots containing passivating agents and surf modifiers are prepared. The process includes reaction of a carbon source, a passivating agent and an additive in a solvent, followed by dialysis and drying, and finally washing and drying in the presence of a surface modifier.
Carbon quantum dots with high fluorescence quantum yield, long fluorescence lifetime, adjustable color, and good compatibility with other materials, improving their application performance in photoconverting materials and anti-counterfeiting materials.
Smart Images

Figure CN119776004A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of light-emitting devices, and in particular to a high-fluorescence modulated carbon quantum dot and a preparation method and application thereof. Background Art
[0002] With the continuous progress of materials science and engineering technology, the demand for environmentally friendly photoconversion materials is very urgent. As a new type of carbon-based photoluminescent carbon material, carbon quantum dots have excellent photoluminescent properties, good biocompatibility, low cytotoxicity, easy synthesis and multiple functional groups on the surface. Therefore, carbon quantum dots have been rapidly developed and applied in the fields of fluorescent bioimaging, therapeutics, detection, light-emitting diodes (LEDs), photocatalysis, anti-counterfeiting, sensing, bioimaging and antibacterial.
[0003] In the field of LED and lighting, carbon quantum dots can be used as a fluorescent conversion layer to prepare LEDs with high lumen efficiency and good color coordinates. White light, as the most common light, has important application needs in the field of optoelectronics, especially in LEDs. However, many reported carbon quantum dots mainly exhibit blue or green fluorescence. At present, in order to obtain carbon quantum dots that emit white light, a common method is to mix multi-color optical discs according to an appropriate mass ratio, but the white fluorescent color prepared by this method has poor stability, and the blue-green-red mixture may also suffer from a strong sense of color block, that is, the color distribution in the lighting scene is uneven, affecting the visual comfort and uniformity of the lighting effect. Therefore, it is very necessary to prepare carbon quantum dots of different colors as needed, that is, this requires that the fluorescent color of the carbon quantum dots has modulatable characteristics.
[0004] In the field of composite materials, adding carbon quantum dots to matrix materials can improve the overall performance of the materials, including mechanical properties, including strength, hardness, wear resistance and electrical conductivity. However, when adding carbon quantum dots to other materials, the compatibility of carbon quantum dots with most materials is relatively poor, and the dispersion in solvents is not good, which may affect the overall performance of the materials. Therefore, it is very necessary to prepare modified carbon quantum dots that have excellent compatibility with matrix materials and are easy to disperse.
[0005] In the field of photocatalysis and energy, carbon quantum dots can improve the efficiency of light energy conversion and improve battery performance. At present, the fluorescence quantum yield of carbon quantum dots prepared by conventional means is extremely low, and most carbon quantum dots are prone to fluorescence quenching effect when aggregated, and the fluorescence lifetime is extremely short, which makes the fluorescence performance of carbon quantum dots less than ideal. Therefore, improving the fluorescence quantum yield of carbon quantum dots and extending their fluorescence lifetime can improve their performance.
[0006] Therefore, in the face of the shortcomings of existing carbon quantum dots and the needs of existing materials, it is necessary to develop a high fluorescence performance carbon quantum dot with high fluorescence quantum yield, long fluorescence lifetime, adjustable color, good compatibility with other materials, and good dispersibility in solvents. Such high fluorescence performance adjustable carbon quantum dots are conducive to expanding their application range. Summary of the invention
[0007] The purpose of the present invention is to provide a highly fluorescent modulated carbon quantum dot and a preparation method and application thereof, so as to solve the technical problems of low fluorescence quantum yield, short fluorescence lifetime and poor compatibility with other materials in the existing preparation method.
[0008] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0009] The present invention provides a highly fluorescent modulated carbon quantum dot, which is prepared from raw materials containing the following mass fractions:
[0010]
[0011] The passivating agent comprises one or more of polyethylene glycol, sodium polystyrene sulfonate, polyacrylamide, polyacrylic acid, polymethyl methacrylate and chitosan;
[0012] The auxiliary agent comprises one or more of amine compounds, carboxylic acid compounds, urea, thiourea and pyridine.
[0013] Furthermore, the amine compound comprises one or more of ethylenediamine, o-phenylenediamine, m-phenylenediamine, p-phenylenediamine, 4-bromo-1,2-diaminobenzene, ethylamine, aniline, dimethylamine and diethylamine; and the carboxylic acid compound comprises one or more of acetic acid, formic acid and benzoic acid.
[0014] Furthermore, the carbon source comprises one or more of citric acid, cellulose, tartaric acid, lignin, folic acid, wood, straw, orange peel, grapefruit peel, glucose, sodium alginate, sucrose, cystine, methionine, lactic acid and oxalic acid.
[0015] Furthermore, the solvent comprises one or more of water, methanol, ethanol, cyclohexane, propylene glycol methyl ether, ethylene glycol butyl ether, N,N-dimethylformamide, formamide, sulfuric acid, N,N-dimethylacetamide, ethyl acetate, dichloromethane, dimethyl sulfoxide and glycerol.
[0016] Further, the surface modifier comprises one or more of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltriethoxysilane, hexadecyltrimethylammonium bromide, 1H,1H,2H,2H-perfluorooctyltriethoxysilane, heptadecafluorodecyltriethoxysilane, perfluorodecyltriethoxysilane, dodecafluoroheptylpropyltrimethoxysilane, sodium alkyl sulfonate of fatty alcohol, alkylamine ester, lauryl phosphate and sodium ethoxylated alkyl sulfate.
[0017] The present invention also provides a method for preparing highly fluorescent modulated carbon quantum dots, comprising the following steps:
[0018] Preparation method without surface modifier in raw materials:
[0019] 1) mixing a carbon source, a passivating agent, and an auxiliary agent in a solvent to react to obtain an initial reaction product;
[0020] 2) The initial reaction product is dialyzed and dried in sequence to obtain highly fluorescent carbon quantum dots;
[0021] Preparation method containing surface modifier in raw materials:
[0022] 3) The highly fluorescent carbon quantum dots obtained in step 2), the solvent and the surface modifier are mixed and reacted, and the reaction products are washed and dried in sequence to obtain highly fluorescent modulatable carbon quantum dots.
[0023] Furthermore, in the step 1), the reaction temperature is 150-250° C., and the reaction time is 5-15 hours.
[0024] Furthermore, in the step 3), the reaction temperature is 50-90° C., and the reaction time is 1-5 h.
[0025] Furthermore, in step 2) and step 3), the drying temperature is independently 100 to 120° C., and the drying time is independently 5 to 24 hours.
[0026] The present invention also provides an application of highly fluorescent modulated carbon quantum dots in light conversion materials and anti-counterfeiting materials.
[0027] Beneficial effects of the present invention:
[0028] The present invention can obtain color-adjustable and stable carbon quantum dots by adjusting the solvent, carbon source and auxiliary agent. The modified carbon quantum dots prepared by the present invention have the characteristics of high fluorescence quantum yield, adjustable wettability, stable and controllable fluorescence color, easy dispersion in organic materials, long service life, etc. The modified carbon quantum dots have the characteristics of long fluorescence quenching time. The carbon quantum dots of the present invention can be used as ideal light conversion materials in fields including photovoltaics, anti-counterfeiting, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The fluorescence lifetime diagram of carbon quantum dots in Comparative Example 1, Example 1, Example 2 and Example 3 of the present invention;
[0030] Figure 2 This is a dispersion diagram of carbon quantum dots in a solvent in Examples 2 and 3 of the present invention;
[0031] Figure 3 Fluorescence images of modulated carbon quantum dots in different embodiments of the present invention. DETAILED DESCRIPTION
[0032] The present invention provides a highly fluorescent modulated carbon quantum dot, which is prepared from raw materials containing the following mass fractions:
[0033]
[0034] The passivating agent comprises one or more of polyethylene glycol, sodium polystyrene sulfonate, polyacrylamide, polyacrylic acid, polymethyl methacrylate and chitosan;
[0035] The auxiliary agent comprises one or more of amine compounds, carboxylic acid compounds, urea, thiourea and pyridine.
[0036] In the present invention, the content of the carbon source is preferably 0.5 to 2.5 parts by mass, and more preferably 0.8 to 1.5 parts by mass.
[0037] In the present invention, the content of the passivating agent is preferably 0.1 to 0.9 parts by mass, and more preferably 0.75 to 0.8 parts by mass.
[0038] In the present invention, the content of the auxiliary agent is preferably 0.5 to 9 parts by mass, more preferably 2.5 to 8 parts, and even more preferably 4.5 to 6 parts.
[0039] In the present invention, the content of the solvent is preferably 20 to 50 parts by mass, and more preferably 20 to 40 parts by mass.
[0040] In the present invention, the content of the surface modifier is preferably 0.5 to 8 parts by mass, more preferably 2.5 to 8 parts, and even more preferably 4.5 to 6 parts.
[0041] In the present invention, the passivating agent is preferably one or more of polyethylene glycol, sodium polystyrene sulfonate, polyacrylamide, polyacrylic acid and polymethyl methacrylate, and more preferably one or more of polyethylene glycol, sodium polystyrene sulfonate and polyacrylamide.
[0042] In the present invention, the amine compound is preferably one or more of ethylenediamine, o-phenylenediamine, m-phenylenediamine, p-phenylenediamine, 4-bromo-1,2-diaminobenzene, ethylamine, aniline, dimethylamine and diethylamine; the carboxylic acid compound is preferably one or more of acetic acid, formic acid and benzoic acid.
[0043] In the present invention, the carbon source is preferably one or more of citric acid, cellulose, tartaric acid, lignin, folic acid, wood, straw, orange peel, grapefruit peel, glucose, sodium alginate, sucrose, cystine, methionine, lactic acid and oxalic acid.
[0044] In the present invention, the solvent is preferably one or more of water, methanol, ethanol, cyclohexane, propylene glycol methyl ether, ethylene glycol butyl ether, N,N-dimethylformamide, formamide, sulfuric acid, N,N-dimethylacetamide, ethyl acetate, dichloromethane, dimethyl sulfoxide and glycerol.
[0045] In the present invention, the surface modifier is preferably one or more of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltriethoxysilane, hexadecyltrimethylammonium bromide, 1H,1H,2H,2H-perfluorooctyltriethoxysilane, heptadecafluorodecyltriethoxysilane, perfluorodecyltriethoxysilane, dodecafluoroheptylpropyltrimethoxysilane, sodium fatty alcohol alkyl sulfonate, alkylamine ester, lauryl phosphate and sodium ethoxylated alkyl sulfate.
[0046] The present invention also provides a method for preparing highly fluorescent modulated carbon quantum dots, comprising the following steps:
[0047] Preparation method without surface modifier in raw materials:
[0048] 1) mixing a carbon source, a passivating agent, and an auxiliary agent in a solvent to react to obtain an initial reaction product;
[0049] 2) The initial reaction product is dialyzed and dried in sequence to obtain highly fluorescent carbon quantum dots;
[0050] Preparation method containing surface modifier in raw materials:
[0051] 3) The highly fluorescent carbon quantum dots obtained in step 2), the solvent and the surface modifier are mixed and reacted, and the reaction products are washed and dried in sequence to obtain highly fluorescent modulatable carbon quantum dots.
[0052] In the present invention, in step 1), the reaction temperature is 150-250° C., preferably 180-220° C., and more preferably 200° C.; the reaction time is 5-15 h, preferably 8-12 h, and more preferably 10 h.
[0053] In the present invention, in the step 3), the reaction temperature is 50-90°C, preferably 60-80°C, and more preferably 70°C; the reaction time is 1-5h, preferably 2-4h, and more preferably 3h.
[0054] In the present invention, in step 2) and step 3), the drying temperature is independently 100 to 120° C., preferably 110° C.; the drying time is independently 5 to 24 hours, preferably 12 to 24 hours.
[0055] The present invention also provides an application of highly fluorescent modulated carbon quantum dots in light conversion materials and anti-counterfeiting materials.
[0056] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0057] Example 1
[0058] Add 2.5g of citric acid and 0.75g of polyethylene glycol to 20g of deionized water respectively, stir until completely dissolved, add 5mL (4.5g) of ethylenediamine dropwise, put the mixture into an autoclave, react at 160°C for 8 hours, cool to room temperature and take out to obtain a light brown liquid. Boil the dialysis bag for activation. Clamp one end of the dialysis bag with a clamp, then put the obtained light brown liquid into the dialysis bag, exhaust the remaining air, and seal the other end with a clamp. Place the dialysis bag in a beaker filled with 1000mL of deionized water, dialyze for 12 hours, and replace the deionized water every 2 hours. The purified liquid is vacuum dried at 100°C for 24 hours, and ground to obtain a light yellow powder. The obtained light yellow powder is a blue fluorescent carbon quantum dot with a fluorescence quantum yield of 96%.
[0059] Example 2
[0060] Add 2.5g of citric acid and 0.75g of polyethylene glycol to 20g of deionized water respectively, stir until completely dissolved, add 5mL (4.5g) of ethylenediamine dropwise, put the mixture into an autoclave, react at 160°C for 8 hours, cool to room temperature and take out to obtain a light brown liquid. Boil the dialysis bag for activation. Clamp one end of the dialysis bag with a clamp, then put the obtained light brown liquid into the dialysis bag, exhaust the remaining air, and seal the other end with a clamp. Put the dialysis bag into a beaker filled with 1000mL of deionized water, dialyze for 12 hours, and replace the deionized water every 2 hours. Vacuum dry the purified liquid at 100°C for 24 hours and grind it to obtain a light yellow powder.
[0061] Add 4g of hexadecyltrimethylammonium bromide to 200g of water to fully dissolve it. Add 2g of the prepared light yellow powder to the above solution. Pour the mixed solution into a flask, stir and heat to 70°C, react for 70 minutes, wash with deionized water, and then vacuum dry at 110°C for 12 hours. The obtained brown powder is a hydrophilic blue fluorescent carbon quantum dot with a fluorescence quantum yield of 52.6% and a water contact angle of less than 20°.
[0062] Example 3
[0063] Add 2.5g of citric acid and 0.75g of polyethylene glycol to 20g of deionized water respectively, stir until completely dissolved, add 5mL (4.5g) of ethylenediamine dropwise, put the mixture into an autoclave, react at 160°C for 8 hours, cool to room temperature and take out to obtain a light brown liquid. Boil the dialysis bag for activation. Clamp one end of the dialysis bag with a clamp, then put the obtained light brown liquid into the dialysis bag, exhaust the remaining air, and seal the other end with a clamp. Put the dialysis bag into a beaker filled with 1000mL of deionized water, dialyze for 12 hours, and replace the deionized water every 2 hours. Vacuum dry the purified liquid at 100°C for 24 hours and grind it to obtain a light yellow powder.
[0064] The prepared 2g light yellow powder was fully dissolved in 20g water, and then 200g ethanol was added, and finally 4g 1H,1H,2H,2H-perfluorooctyltriethoxysilane was added. The mixed solution was poured into a flask, stirred and heated to 90°C, reacted for 120 minutes, washed with deionized water, and then vacuum dried at 110°C for 8 hours. The obtained brown powder was a hydrophobic blue fluorescent carbon quantum dot with a fluorescence quantum yield of 67%, and a water contact angle of more than 90°.
[0065] Example 4
[0066] Add 0.15g of citric acid, 0.05g of polyethylene glycol and 0.3g of o-phenylenediamine to 20g of ethanol respectively, stir until completely dissolved, put the mixture into an autoclave, react at 200°C for 10 hours, cool to room temperature and take out to obtain a brown liquid. Boil the dialysis bag for activation. Clamp one end of the dialysis bag with a clamp, then put the obtained light brown liquid into the dialysis bag, exhaust the remaining air, and seal the other end with a clamp. Place the dialysis bag in a beaker filled with 1000mL of deionized water, dialyze for 12 hours, and replace the deionized water every 2 hours. The purified liquid is vacuum dried at 100°C for 24 hours and ground to obtain a black powder. The obtained black powder is a light purple fluorescent carbon quantum dot with a fluorescence quantum yield of 65.2%.
[0067] Example 5
[0068] 0.15g of citric acid, 0.05g of polyethylene glycol and 0.3g of o-phenylenediamine were added to 20g of N,N-dimethylformamide respectively, stirred until completely dissolved, and the mixture was placed in an autoclave, reacted at 200°C for 10 hours, and taken out after cooling to room temperature to obtain a brown liquid. The dialysis bag was boiled for activation. One end of the dialysis bag was clamped with a clamp, and then the obtained dark green liquid was placed in the dialysis bag, the remaining air was exhausted, and the other end was sealed with a clamp. The dialysis bag was placed in a beaker filled with 1000mL of deionized water, dialyzed for 12 hours, and the deionized water was replaced every 2 hours. The purified liquid was vacuum dried at 100°C for 24 hours, and ground to obtain a green powder. The obtained green powder was a green fluorescent carbon quantum dot with a fluorescence quantum yield of 59.6%.
[0069] Example 6
[0070] 0.15g of citric acid, 0.05g of polyethylene glycol and 0.3g of o-phenylenediamine were added to 20mL of 6.1mol / L dilute sulfuric acid solution respectively, stirred until completely dissolved, and the mixture was placed in an autoclave, reacted at 200°C for 10 hours, and taken out after cooling to room temperature to obtain a brown liquid. The dialysis bag was boiled for activation. One end of the dialysis bag was clamped with a clamp, and then the obtained dark green liquid was placed in the dialysis bag, the remaining air was discharged, and the other end was sealed with a clamp. The dialysis bag was placed in a beaker filled with 1000mL of deionized water, dialyzed for 12 hours, and the deionized water was replaced every 2 hours. The purified liquid was vacuum dried at 100°C for 24 hours, and ground to obtain a black powder. The obtained black powder was white fluorescent carbon quantum dots with a fluorescence quantum yield of 73%.
[0071] Comparative Example 1
[0072] Add 2.5g of citric acid to deionized water, stir until completely dissolved, add 5mL (4.5g) of ethylenediamine dropwise, put the mixture into an autoclave, react at 160°C for 8 hours, cool to room temperature and take out to obtain a light brown liquid. Boil the dialysis bag for activation. Clamp one end of the dialysis bag with a clamp, then put the obtained light brown liquid into the dialysis bag, exhaust the remaining air, and seal the other end with a clamp. Place the dialysis bag in a beaker filled with 1000mL of deionized water, dialyze for 12 hours, and replace the deionized water every 2 hours. Vacuum dry the purified liquid at 100°C for 24 hours, grind to obtain a light yellow powder, and the obtained light yellow powder is a blue fluorescent carbon quantum dot with a quantum yield of only 5.8%.
[0073] Figure 1 It is the fluorescence lifetime graph of carbon quantum dots in comparative example 1, example 1, example 2 and example 3. Through analysis, it can be known that the fluorescence lifetime of ordinary carbon quantum dots without surface passivation or surface modification is 6.18ns, the fluorescence quantum yield of carbon quantum dots without modification is very low, and the fluorescence lifetime is very short, while the fluorescence lifetime of carbon quantum dots with surface passivation reaches 8.42ns, and the fluorescence lifetime of carbon quantum dots with surface modification reaches 15.57ns and 16.09ns respectively, and the fluorescence lifetime of modified carbon quantum dots is long.
[0074] Figure 2 This is a dispersion diagram of carbon quantum dots in the solvent in Example 2 and Example 3 of the present invention. The cuvette on the left in the figure is a dispersion of carbon quantum dots. Obviously, the modified carbon quantum dots have good dispersibility in the solvent and no agglomeration occurs. Fluorescence is evenly released from the dispersion without obvious fluorescent particles.
[0075] Figure 3 1 is a fluorescence color diagram of multi-color carbon quantum dots in different embodiments. From left to right in the figure are carbon quantum dots in embodiment 1, embodiment 4, embodiment 5, and embodiment 6, and their colors are dark blue, light purple, green, and white, respectively.
[0076] It can be seen from the above embodiments that the present invention provides a highly fluorescent modulated carbon quantum dot and a preparation method and application thereof. The present invention can obtain color-adjustable and stable carbon quantum dots by adjusting the solvent, carbon source and additives. The modified carbon quantum dots prepared by the present invention have the characteristics of high fluorescence quantum yield, adjustable wettability, stable and controllable fluorescence color, easy dispersion in organic materials, and long service life. The modified carbon quantum dots have the characteristic of long fluorescence quenching time. The carbon quantum dots of the present invention can be used as an ideal light conversion material in fields including photovoltaics and anti-counterfeiting.
[0077] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A highly fluorescent modulatable carbon quantum dot, characterized in that: Prepared from the following raw materials in parts by weight: The passivating agent comprises one or more of polyethylene glycol, sodium polystyrene sulfonate, polyacrylamide, polyacrylic acid, polymethyl methacrylate and chitosan; The auxiliary agent comprises one or more of amine compounds, carboxylic acid compounds, urea, thiourea and pyridine.
2. The highly fluorescent modulatable carbon quantum dots according to claim 1, characterized in that: The amine compound includes one or more of ethylenediamine, o-phenylenediamine, m-phenylenediamine, p-phenylenediamine, 4-bromo-1,2-diaminobenzene, ethylamine, aniline, dimethylamine and diethylamine; the carboxylic acid compound includes one or more of acetic acid, formic acid and benzoic acid.
3. The highly fluorescent modulatable carbon quantum dots according to claim 1 or 2, characterized in that: The carbon source comprises one or more of citric acid, cellulose, tartaric acid, lignin, folic acid, wood, straw, orange peel, grapefruit peel, glucose, sodium alginate, sucrose, cystine, methionine, lactic acid and oxalic acid.
4. The highly fluorescent modulated carbon quantum dots according to claim 3, characterized in that: The solvent comprises one or more of water, methanol, ethanol, cyclohexane, propylene glycol methyl ether, ethylene glycol butyl ether, N,N-dimethylformamide, formamide, sulfuric acid, N,N-dimethylacetamide, ethyl acetate, dichloromethane, dimethyl sulfoxide and glycerol.
5. The highly fluorescent modulated carbon quantum dots according to claim 1, 2 or 4, characterized in that: The surface modifier comprises one or more of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltriethoxysilane, hexadecyltrimethylammonium bromide, 1H,1H,2H,2H-perfluorooctyltriethoxysilane, heptadecafluorodecyltriethoxysilane, perfluorodecyltriethoxysilane, dodecafluoroheptylpropyltrimethoxysilane, sodium fatty alcohol alkyl sulfonate, alkylamine ester, lauryl alcohol phosphate and ethoxylated sodium alkyl sulfate.
6. The method for preparing highly fluorescent modulated carbon quantum dots according to claims 1 to 5, characterized in that: The following steps are involved: Preparation method without surface modifier in raw materials: 1) mixing a carbon source, a passivating agent, and an auxiliary agent in a solvent to react to obtain an initial reaction product; 2) The initial reaction product is dialyzed and dried in sequence to obtain highly fluorescent carbon quantum dots; Preparation method containing surface modifier in raw materials: 3) The highly fluorescent carbon quantum dots obtained in step 2), the solvent and the surface modifier are mixed and reacted, and the reaction products are washed and dried in sequence to obtain highly fluorescent modulatable carbon quantum dots.
7. The preparation method according to claim 6, characterized in that: In the step 1), the reaction temperature is 150-250° C. and the reaction time is 5-15 hours.
8. The preparation method according to claim 6 or 7, characterized in that: In the step 3), the reaction temperature is 50-90° C. and the reaction time is 1-5 hours.
9. The preparation method according to claim 8, characterized in that: In the step 2) and the step 3), the drying temperature is independently 100 to 120° C., and the drying time is independently 5 to 24 hours.
10. Use of the highly fluorescent modulated carbon quantum dots according to claims 1 to 5 in light conversion materials and anti-counterfeiting materials.
Citation Information
Patent Citations
Preparation method of carbon quantum dots with high fluorescence property
CN103342347A
Preparation technology of seven-color fluorescent carbon quantum dots
CN110342490A
Carbon quantum dot fluorescent anti-forgery ink as well as preparation method and application thereof
CN114752257A
Solid fluorescent carbon quantum dot material and preparation method thereof
CN115491197A
Novel nitrogen-doped carbon dot modified carbon nitride as well as preparation method and application thereof
CN117920304A
Cited By
Method for preparing coal pitch-based modified carbon quantum dots in methanol-water mixed solvent system
CN120888301A